Chronic morbidity and health seeking behavior among post-menopausal women of Itahari Sub-Metropolitan City, Nepal - Sharma, Pramita; Ghimire, Anup (Journal of Patan Academy of Health Sciences, 2023)
Introduction: The prevalence of morbidity increases in postmenopausal period. Usually co-morbid chronic conditions and symptoms of menopause are underestimated due to low awareness thereby affecting the health seeking behaviour. This study aims to find out the chronic morbidity and health seeking behaviour among post-menopausal women of Itahari sub metropolitan city of Nepal. Method: This is a community based cross-sectional study conducted in 5 wards of Itahari sub metropolitan city, of Nepal over a period of one year (February 2018 to January 2019) among 490 post-menopausal women of 45 and above age. Ethical approval was obtained. The frequency and percentage of women with chronic morbidity and their health seeking in general was calculated. Also, percentage of health seeking for the each morbidly and postmenopausal symptoms were calculated using MS-Excel. Result: Among the 490 participants 69.4% were having chronic diseases in which diabetes mellitus and hypertension had highest prevalence. Up to 98% of the women having chronic morbidity sought help from professionals. There was lowest professional health seeking for psychological symptoms and highest for somatic symptoms. Conclusion: Our study shows high chronic morbidity in post-menopausal period and good health seeking behaviour for them. There is less professional heath seeking for vasomotor and psychological symptoms of post menstrual period.